Perlindungan Konsumen terhadap Makanan Impor Tanpa Label Bahasa Indonesia yang Dijual Melalui E-Commerce bagi Penjual serta Konsumen di Indonesia - Verga Syaharani Sukma; Lia Nuraini; Muhammad Fajar Hidayat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid growth of e-commerce in Indonesia has led to significant changes in the way food products are sold, particularly imported foods. While the convenience of online shopping offers great benefits to both consumers and businesses, it has also uncovered several regulatory challenges, especially concerning the labeling of imported food products. A critical issue is the non-compliance with the Indonesian language labeling requirements for these products, which puts consumers at a disadvantage. Such practices not only violate existing consumer protection laws but also pose risks to public health, as consumers may not fully understand the contents or risks associated with foreign food products due to language barriers. This study highlights the need for a more robust framework to enforce labeling laws, focusing on the responsibility of e-commerce platforms. Platforms play a crucial role in bridging the gap between sellers, manufacturers, and consumers. By implementing stricter oversight and monitoring mechanisms, e-commerce platforms could ensure that sellers comply with legal labeling requirements. Furthermore, platforms can act as intermediaries to facilitate consumer complaints and provide dispute resolution services in cases of non-compliance. In addition, the study emphasizes the importance of consumer education. Many consumers are unaware of their rights and the standards they should expect from food products sold online. Thus, there is a need for awareness campaigns and easy access to information on consumer rights, particularly in the context of e-commerce. Strengthening the enforcement of these regulations, providing training for business actors, and improving public awareness will help ensure that imported food products are sold in a transparent, legally compliant manner.